Ovaric Abscess: Genesis or Complication? - Martínez, Bertha Zenaida Acevedo; Sánchez, Morelos Adolfo García; París, Romero Angeles Bruno; Rodríguez, Alejandro Giovanni Hernández; López, Zarú Isaac Urrutia; Rodríguez, Estephanie Marisol Hernández; Velela, Cinthia Jocxamani Morales; Rosas, Areli Stephanie Delia Hernández (British Journal of Healthcare and Medical Research, 2024)
Introduction: An ovarian abscess is defined as a complex infectious tumor of the adnexa of the uterus, which commonly forms as a sequel of an inflammatory pelvic disease, this disease being potentially fatal. Objective: Presentation of a case. Method: A 35-year-old female who underwent a vaginal hysterectomy 20 days ago, with clinical evidence of septic shock G II and acute abdomen, was admitted to the operating room for emergency surgery, in the exploratory laparotomy with findings of 800 milliliters of foul-smelling purulent material and ovarian abscess. Discussion: in the case of an ovarian abscess with a medical history and an exquisite physical examination and thus, issue a diagnosis, forced to rule out other pathologies. Surgical treatment is therefore the best recognized option when medical treatment fails in ovarian abscesses, however, cases must be selected and separated from patients with pelvic inflammatory disease, and consequently varies from asymptomatic cases to severe sepsis. Conclusions: Ovarian abscess should be diagnosed correctly and abstained from medical treatment, since like any abscess, its surgical drainage and ablation is a priority, imminent and forceful for a complete cure.